Coming to Our Senses beyond the Talking-Head: the Panesthetic Documentary Interview - Carbonell, Isabelle (2018)
Documentary interview methodologies are often oversimplified and undertheorized, and talking-heads, the technique most strongly associated with the documentary interview, is often perceived as the sole technique for interviewing while it is only one among many. Alternate methodologies are possible, that take into account the sensorial world, moving beyond the talking-head. Encompassing a multisensory approach not only to interview but also to the entire filmmaking process, I have developed a new method of interviewing called the panesthetic method. Baffle Their Minds with Bullsh*t, Kerry Leigh (2013) features a talking head interview style, while in The Blooming (working title), I stay connected by a lav microphone for over 18+ hours on a boat to Wynn, my interviewee. In contrasting these two case studies, the panesthetic approach emerges as a methodological path to rethinking the documentary interview.